Biological age in critical care: current evidence, future prospects, and clinical implications - Jiang, Li-bing; Han, Wen (Frontiers in Medicine, 2025)
Accurate assessment of critically ill patients is essential for informing treatment decisions and predicting outcomes. While chronological age—defined by the number of years lived—is commonly used in clinical practice, it does not necessarily capture a patient’s true physiological status. In contrast, biological age, which reflects genetic, environmental, and lifestyle factors, offers a more precise indicator of overall health. Emerging evidence supports its potential as a robust predictor of mortality, intensive care readmission, and disease severity in conditions such as sepsis and respiratory failure. Notably, unlike the linear progression of chronological age, biological age can fluctuate in response to acute stress and may revert to lower levels if the patient’s condition improves. This dynamic property underscores the utility of biological age in guiding invasive procedures, refining medication strategies, and optimizing nutrition and rehabilitation. The present study provides an overview of the definitions and methods used to calculate biological age, examines its current applications in critical care, and discusses its prospective roles in intensive care unit.